Oral drug composition for vascular endothelial growth factor inhibitor - WANG SHULI; CHEN LIYING; HE GUANGJIE; SUN LIANG; LI JING; YANG XINYI; HU XIAOYUN (2017)
The invention belongs to the medical field, particularly relates to an oral drug composition for inhibiting salt of a compound of formula I (shown in the description) of a VEGF, pharmaceutical use of the oral drug composition and a pharmaceutical preparation and particularly aims at treatment of tumors and angiogenesis. The invention further relates to a synthetic method of the compound. 本发明属于医药领域，特别涉及抑制VEGF的式Ⅰ化合物的盐口服药物组合物，在药物上的用途和药用制剂，特别是针对肿瘤、血管新生的治疗。本发明也涉及该化合物的合成方法。